ABUSIVE TREATMENTS DURING CHILDHOOD AS THE CAUSE OF DISSOCIATIVE IDENTITY DISORDER SUFFERED BY LAURIE IN CLARKâ€™S NOVEL ALL AROUND THE TOWN - Eva Fatimah (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2017)
This paper discusses the causes of dissociative identity disorder suffered by the character of Laurie inMarkâ€™s novel â€œAll around the Townâ€by applying a literary psychological approach. The objective of this study is to disclose the causes of disassociative identity disorder in Laurieâ€™s personality. This is a library research as as the whole data were taken from the text of the novel. The research method applied in this study was qualitive. Text method analysis was used to identify the causes of of disassociative identity disorder suffered byLaurie. This study applied literary psychological approach by adopting Dellâ€™s and Putnamâ€™s clinical psychology theories on Disassociative Identity Disorder. The results of the study show that the causes of the disassociative identity disorder in Laurieâ€™s personality are the abusive treatments she suffered during her childhood time when she was kidnapped, the lateness of medical treatment, and the new severe trauma.Keywords: alternative identity, Dissociative identity disorder, psychological approach